The genome sequence of the European water vole, Arvicola amphibius Linnaeus 1758 [version 1; peer review: 2 approved] - Michael A. Quail (Wellcome Open Research, 2021)
We present a genome assembly from an individual male Arvicola amphibius (the European water vole; Chordata; Mammalia; Rodentia; Cricetidae). The genome sequence is 2.30 gigabases in span. The majority of the assembly is scaffolded into 18 chromosomal pseudomolecules, including the X sex chromosome. Gene annotation of this assembly on Ensembl has identified 21,394 protein coding genes.